Biomineralization of Pd nanoparticles using Phanerochaete chrysosporium as a sustainable approach to turn platinum group metals (PGMs) wastes into catalysts. (September 2019) - Tarver, Sophie; Gray, Daniel; Loponov, Konstantin; Das, Diganta B.; Sun, Tao; Sotenko, Maria
Abstract: Due to the increasing demand for recovery of precious metals from waste streams, the role of fungus as a potential adsorbent is growing. Thus, this research aimed to develop a novel method for the biomineralization of palladium nanoparticles using Phanerochaete chrysosporium fungus. The adsorption of palladium onto the fungal mycelium was studied by adding palladium salt at 12–48 ppm to the fermentation medium following the fungal growth. Amide groups of chitin and proteins on the surface of the fungus are believed to coordinate palladium cations yielding Freundlich-type competitive adsorption isotherm. The adsorption capacity was found to reach 22-128 mgPd g −1 of dried fungal biomass. Biomineralization of palladium from an aqueous solution led to the formation of extracellular well defined Pd nanoparticles of 10–14 nm confirmed by XPS, TEM and XRD analyses. The biologically synthesised nanoparticles were found to perform equally well to a Pd/C commercial catalyst in a Heck reaction of styrene and iodobenzene. This is the first reported use of Phanerochaete chrysosporium to synthesise palladium nanoparticles and confirmation of their resulting catalytic activity. The presented example paves the way for the development of fungi-based membranes to be used in the palladium recovery from industrial effluents. Graphical abstract: Image 1 Highlights: Phanerochaete chrysosporium fungus was shown to reduce Pd from aqueous solutions. The adsorption of Pd onto the fungus followed Freundlich competitive adsorption. XPS, XRD and TEM methods confirmed the formation of well-defined Pd nanoparticles. Bio Pd nanoparticles are supported onto the fungal mycelium. Bio Pd nanoparticles were shown to catalyse the Heck reaction of stilbene formation.